Sequencing of Candidate Genes Selected by Beta Cell Experts in Monogenic Diabetes of Unknown Aetiology - Edghill, Emma L; Minton, Jayne A L; Groves, Christopher J; Flanagan, Sarah E; Patch, Ann-Marie; Rubio-Cabezas, Oscar; Shepherd, Maggie; Lenzen, Sigurd; McCarthy, Mark I; Ellard, Sian; et al. (JOP. Journal of the Pancreas, 2016)
Context Approximately 39% of cases with permanent neonatal diabetes (PNDM) and about 11% with maturity onset diabetes of the young (MODY) have an unknown genetic aetiology. Many of the known genes causing MODY and PNDM were identified as being critical for beta cell function before their identification as a cause of monogenic diabetes. Objective We used nominations from the EU beta cell consortium EURODIA project partners to guide gene candidacy. Subjects Seventeen cases with permanent neonatal diabetes and 8 cases with maturity onset diabetes of the young. Main outcome measures The beta cell experts within the EURODIA consortium were asked to nominate 3 "gold", 3 "silver" and 4 "bronze" genes based on biological or genetic grounds. We sequenced twelve candidate genes from the list based on evidence for candidacy. Results Sequencing ISL1, LMX1A, MAFA, NGN3, NKX2.2, NKX6.1, PAX4, PAX6, SOX2, SREBF1, SYT9 and UCP2 did not identify any pathogenic mutations. Conclusion Further work is needed to identify novel causes of permanent neonatal diabetes and maturity onset diabetes of the young utilising genetic approaches as well as further candidate genes. Image: Peninsula Medical School logo. Exeter, United Kingdom.